Evaluating Smart House Adaptability Potentials of Residential Buildings in Famagusta, North Cyprus - Esmaili, Nima (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Future of buildings and the built environment is a predictable term. Predicting the future of building design is mainly related to the developments in Internet of Things (IT) and new developing technologies. Users of buildings demand to update their living spaces with new technologies to ease their daily life, this process makes changes in the function of building, architectural spaces, facilities, home automation gadgets and devices. Adaptability is known as an environmentally friendly answer to the mentioned changes, adaptability extends the useful age of building and it delays the need to construction a new building and lowers the rate of building demolitions and obsolescence. According to the previous academic literature, the future of building will be related to ‘Smart’ and ‘Intelligent’ terms. As a result, in this thesis the adaptability of buildings is going to respond to the new needs from smart and intelligent upgrades of a future building. There is a lack of literature over discovering adaptability potentials of an existing building which is going to be smart house in the future. This thesis researched 12 different smart and intelligent features through the literature review over the topic. The aim of this thesis is to categorize the definitions and features of smart house and then evaluate the potential of smart house adaptability of an existing building, the source of change is considered as the future developments of technology in building. This study reviews recent literature over the building adaptability and smart houses. At the end a case study evaluates the adaptability potential of residential buildings in Famagusta, North Cyprus. Keywords: adaptable building, residential building, house, smart house, technology.

ÖZ:Binaların ve yapılı çevrenin geleceği tahmin edilebilir bir terimdir. Bina tasarımının geleceğini tahmin etmek esas olarak Nesnelerin İnterneti (Nİ) ve yeni gelişen teknolojilerdeki gelişmelerle ilgilidir. Binaların kullanıcıları günlük yaşamlarını kolaylaştırmak için yaşam alanlarını yeni teknolojilerle güncellemek isterler, bu süreç bina, mimari mekanlar, tesisler, ev otomasyon alet ve cihazlarının işlevinde değişiklikler yapar. Uyarlanabilirlik, bahsedilen değişikliklere çevre dostu bir cevap olarak bilinir, uyarlanabilirlik binanın yararlı yaşını uzatır ve yeni bir bina inşa etme ihtiyacını geciktirir ve bina yıkım ve eskime oranını düşürür. Önceki akademik literatüre göre, inşa etmenin geleceği "Akıllı" ve "Zeki" terimleriyle ilişkili olacaktır. Sonuç olarak, bu tezde binaların uyarlanabilirliği, gelecekteki bir binanın akıllı ve zeki yükseltmelerinden gelen yeni ihtiyaçlara cevap verecektir. Gelecekte akıllı ev olacak mevcut bir binanın uyarlanabilirlik potansiyellerini keşfetme konusunda literatür eksikliği var. Bu tez, konu üzerine literatür taraması yoluyla 12 farklı akıllı ve zeki özelliği araştırdı. Bu tezin amacı, akıllı evin tanımlarını ve özelliklerini kategorize etmek ve daha sonra mevcut bir binanın akıllı ev uyarlanabilirlik potansiyelini değerlendirmektir, değişimin kaynağı yapıdaki teknolojinin gelecekteki gelişmeleri olarak kabul edilir. Bu çalışma, bina uyarlanabilirliği ve akıllı evler hakkındaki son literatürü gözden geçirmektedir. Sonunda bir analiz çalışması, Kuzey Kıbrıs'ın Gazimağusa kentindeki konutların uyarlanabilirlik potansiyelini değerlendiriyor. Anahtar kelimeler: uyarlanabilir bina, konut binası, ev, akıllı ev, teknoloji.
Master of Science in Interior Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2020. Supervisor: Assoc. Prof. Dr. Afet Çeliker Coşkun.
Keywords: Architecture; Domestic